2022
DOI: 10.19090/pp.v15i1.2357
|View full text |Cite
|
Sign up to set email alerts
|

"Attention please!": The dark side of dancers’ personality

Abstract: The present study aims to investigate the dark side of dancers’ personality. In recent literature, dark personality traits were conceptualized as the Dark Tetrad which includes Machiavellianism, narcissism, psychopathy and sadism. The participants in this study were 98 dancers, aged between 18 and 57 (M = 34.71, SD = 11.21; 86.7% women), who practiced different dance types (classical ballet, modern dance, flamenco, oriental dance, hip-hop, salsa, tango, merengue, bachata and Latin dances-samba, rumba) both pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Human body is the basic instrument of dance since the dancer communicates with others using his/her movements. As previous studies have shown, dance has a great potential to be a medium of communication of various feelings, needs, ideas, intentions, concepts and bodily sensations (Christensen, et al, 2017;Džadžević, 2005;Hanna, 1995;Maletić, 1986;Vukadinović, 2013Vukadinović, , 2022Vukadinović & Marković, 2017, 2022. By dancing spontaneously, people can communicate the widest range of their feelings and states expressing them with body movements.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Human body is the basic instrument of dance since the dancer communicates with others using his/her movements. As previous studies have shown, dance has a great potential to be a medium of communication of various feelings, needs, ideas, intentions, concepts and bodily sensations (Christensen, et al, 2017;Džadžević, 2005;Hanna, 1995;Maletić, 1986;Vukadinović, 2013Vukadinović, , 2022Vukadinović & Marković, 2017, 2022. By dancing spontaneously, people can communicate the widest range of their feelings and states expressing them with body movements.…”
Section: Introductionmentioning
confidence: 99%
“…It is a system of organized and formalized movements which the artist consciously expresses and deliberately conveys to the observer (see more in: Blom & Chaplin, 2000;Carter, 1998;Džadžević, 2005;Jowit, 1994;Layson, 1994;Meekums, 2005;Tufnel & Crickmay, 2006;Vukadinović, 2019). In search for understanding the motivation for dancing, various authors have addressed the question of why people dance or what drives them to perform this universal human activity (Christensen, Cela-Conde, & Gomila, 2017;Lovatt, 2016Lovatt, , 2018Maletić, 1986;Maraz, Király, Urbán, Griffiths & Demetrovics, 2015, Vukadinović, 2019, 2022. Many answers to these questions have been given from the standpoint of different approaches and from various perspectives including psychological, historical, anthropological, sociological, evolutionary, cultural, artistic, neurobiological and medical ones.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations